The Role of Oxidative Stress in Suicidal Behaviour Among Bipolar Patients: A Cross-Sectional Study in a Malaysian Sample - Loo, Jiann Lin; Mohamad Kamal, Nurul Ain; Goon, Jo Aan; Ahmad Damanhuri, Hanafi; Tan, Jaclyn Ai Chin; Abdul Murad, Nor Azian; Shah, Shamsul Azhar; Sulaiman, Siti Aishah; Fazry, Shazrul; Sharip, Shalisah; Mohamed Saini, Suriati; Gunasekaran, Geetha; et al. (Frontiers in Psychiatry, 2021)
Background: Oxidative stress markers are found to link with depression and suicide attempts in bipolar disorder(BD) although the role of DNA damage as a marker of suicidal ideation and attempt has yet to be determined. We aim to investigate the association between DNA damage and suicidal behaviour i.e. suicidal ideation & suicide attempt among suicide ideators in BD patients while accounting for clinical and psychosocial risk factors. Methods: A cross-sectional study was conducted in the University Kebangsaan Malaysia Medical Centre on 62 consecutive BD patients diagnosed using the M.I.N.I. Neuropsychiatric Interview and 26 healthy control participants. Socio-demographic and clinical assessments were performed using the Columbia Suicide Severity Rating Scale (C-SSRS) for lifetime suicidal ideation and attempt, Quick Inventory of Depressive Symptomatology (QIDS) for depression severity, Clinical Global Impression for Bipolar Disorder (CGI-BD) for illness severity (both mania, CGI-Mania and major depressive episode, CGI-MDE), Social Readjustment Rating Scale (SRRS) for change in life events, and Barratt Impulsivity Scale (BIS) for behavioural impulsivity. The degree of DNA damage in peripheral blood samples was determined using a standard protocol of comet assay. Results: Multivariable logistic regression revealed higher scores of CGI-MDE as the sole significant factor for lifetime suicidal ideation (OR=1.937, 95%CI=1.799-2.076). Although initial bivariable analysis showed a significant association between DNA damage, MDA, CAT and suicidal behaviour, the findings were not seen in multivariable logistic regression. Bivariable subgroup analysis showed that moderate and severe DNA damage (p=0.032 and p=0.047 respectively) were significantly associated with lifetime suicide attempts among lifetime suicide ideators. The study is the first to look at the connection between DNA damage and suicidal risk in bipolar patients. It is limited by the small sample size and lack of information on illicit substance use. Conclusions: More severe DNA damage was significantly associated with lifetime suicide attempts among lifetime suicide ideators in BD. However, the severity of depression was found to be independently associated with lifetime suicidal ideation per se rather than DNA damage in BD. Larger prospective studies are required to ascertain the potential of DNA damage as a biomarker for the transition from suicidal ideation to a suicide attempt.